PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2010-2012) - Arsanto Teguh Utomo; Rahardjo Rahardjo (Diponegoro Journal of Accounting, 2014)
Starting from agency theory and develop good corporate governance principles of transparency accountability, responsibility, independence and fairness, this study aimed to examine the effect of corporate governance mechanisms on financial performance.The population of this study are all companies listed on the stock exchanges of Indonesia, which reported annual reports from 2010-2012 , the total study observation was 77. This research is a quantitative study using multiple regression analysis and descriptive analysis . Multiple regression analysis was used to test the mechanisms of good corporate governance ( institutional ownership , the board , audit committee and audit quality ) on financial performance . While the descriptive analysis is used to see the tendency of each of the study variables . In this study using ROA to analyze the performance of the company(financial). . The results show that institutional ownership , board size and independent directors has no effect on the financial performance while managerial ownership and board size significantly influence financial performance .